Kumon attendance system using RFID / Hadirah Irdina Helimi - Helimi, Hadirah Irdina (2020)
KUMON is the largest and most well-known self-learning enrichment centre in the world with over 4 million students currently enrolled across 51 countries and regions. It has established a strong recognition in Malaysia by helping thousands of Malaysian children self-learn and self-develop their potential. In addition, Kumon Kota Bharu have been established in year 2014 and currently have 100 students from different level of grades. Presently, Kumon Kota Bharu center does not have a proper system for monitoring their students’ attendance. It still practicing manual way of taking manually appearance and also detail of student information still on paper which less secure. Therefore, the objective of research is to develop Kumon Attendance System using Radio Frequency Identification that tested at Kumon center with 30 respondents. The methodology phase using agile method by implementing the waterfall mode that used to identify and analyse information about the project. It consists of five phase methodology which is information gathering, planning, design and development, testing and evaluation and documentation. The result presented contains functionality test and usability test. Functionality performed due to analysed the system if there are bugs or error during the system. In order to conduct the usability test, a set of the questionnaire was distributed among parents and kumon center owner. The result found that 53.3% participant agreed that the system is beneficial to be implemented in Kumon center throughout Malaysia.